Analysis of Decisions on Cases Granting Child Custody to Biological Fathers - Syahrial Nugraha Rahman (Estudiante Law Journal, 2026)
The purpose of this research is to find out how to review the determination of child custody based on laws and regulations. The type of research used in this study is normative legal research, namely a type of legal research obtained from literature studies, by analyzing a legal issue through statutory regulations, court decisions, research on literature and other reference materials related to Revocation of child custody as stated in decision No. 470/Pdt.G/2022/PA.Gtlo. The results of this study indicate the Islamic concept of child custody known as hadanah, the criteria for divorce, explicitly it is the mother who is given the right to care for the child according to the rules, that the child is not yet mumayyiz and if the mother does not meet the requirements as the holder of custody, then the right foster care is transferred to the closest relative who fulfills the requirements, as required by article 156 of the Compilation of Islamic Law (KHI). As for custody of children who are mumayyiz, they are given the option to choose between the father or the mother. However, the option right is not absolute. This means that the child's choice can be granted as long as the person chosen has the ability to guarantee the physical and spiritual safety of the child he is caring for. Between Islamic law, the Compilation of Islamic Law (KHI), Law No. 1 of 1974 concerning marriage, international conventions and several laws, there is a similarity of view between the principle of the best interests of children which is based more on considerations of benefit. Juridically, if there is a dispute regarding child custody for those who have not mumayyiz, then the court will decide based on the interests of the child.